From structure prediction to function: defining the domain on the African swine fever virus CD2v protein required for binding to erythrocytes - Ana Luisa Reis; Anusyah Rathakrishnan; Vlad Petrovan; Muneeb Islam; Lynnette Goatley; Katy Moffat; Mai Tuyet Vuong; Yuan Lui; Simon J. Davis; Shinji Ikemizu; Linda K. Dixon (mBio)
ABSTRACT African swine fever virus (ASFV) is a high-consequence pathogen posing a substantial threat to global food security. This large DNA virus encodes more than 150 open reading frames, many of which are uncharacterized. The EP402R gene encodes CD2v, a glycoprotein expressed on the surface of infected cells and the only viral protein known to be present in the virus external envelope. This protein mediates binding of erythrocytes to both cells and virions. This interaction is known to prolong virus persistence in blood thus facilitating viral transmission. The sequence of the extracellular domain of CD2v shows similarity with that of mammalian CD2 proteins and is therefore likely to feature two immunoglobulin (Ig)-like domains. A combination of protein structure modeling and extensive mutagenesis was used to identify residues mediating binding of transiently expressed CD2v to erythrocytes. The N-terminal Ig-like domain AGFCC′C″ β sheet was identified as the putative CD2v erythrocyte-binding area. This region differed from the putative CD58 ligand binding site of host CD2, suggesting that CD2v may bind to a ligand(s) other than CD58. An attenuated genotype I ASFV was constructed by replacing the wild-type EP402R gene for a mutant form expressing CD2v bearing a single amino acid substitution, which abrogated the binding to erythrocytes. Pigs immunized with the recombinant virus developed early antibody and cellular responses, low levels of viremia, mild clinical signs post-immunization, and high levels of protection against challenge. These findings improve our understanding of virus–host interactions and provide a promising approach to modified live vaccine development.IMPORTANCEA better understanding of the interactions between viruses and their hosts is a crucial step in the development of strategies for controlling viral diseases, such as vaccines and antivirals. African swine fever, a pig disease with fatality rates approaching 100%, causes very substantial economic losses in affected countries, and new control measures are clearly needed. In this study, we characterized the interaction between the ASFV CD2v protein and host erythrocytes. The interaction plays a key role in viral persistence in blood since it can allow the virus to “hide” from the host immune system. We identified the amino acids in the viral protein that mediate the interaction with erythrocytes and used this information to construct a mutant virus that is no longer able to bind these cells. This virus induces strong immune responses that provide high levels of protection against infection with the deadly parental virus.